The Law on transfer and business taxation : with illustrations, problems, and solutions - De Leon, Hector S.; De Leon, Hector S. Jr. (Manila, Philippines : Rex Book Store, 2016)
Intended primarily as a textbook in colleges and universities, it has been designed likewise to serve as useful reference or guide not only to tax officials and practitioners but also to the young businessmen and the ordinary tax payers who have no previous background on the subject. It will be noticed that in many cases the book does not limit itself to a mere discussion or explanation of theoretical principles and rules on transfer and business taxation. Illustrations, tax computations, and solutions to hypothetical tax problems are also supplied to further facilitate understanding of the law.
Part I Transfer Taxation -- Chapter 1- Estate Tax -- Chapter 2 - Donor's Tax -- Part II Business Taxation -- Chapter 1 - In General -- Chapter 2 - Value-Added Tax -- Chapter 3 - Other Percentage Taxes -- Chapter 4 - Excise taxes on certain goods -- Chapter 5 - Documentary Stamp Taxes -- Chapter 6 - Statutory Offenses and Penalties -- Chapter 7 - Compliance Requirements -- Chapter 8 - Local Taxation.
Keywords: BUSINESS ENTERPRISES -- TAXATION LAW AND LEGISLATION -- PHILIPPINES